(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article the state of teaching of graphic disciplines is examined in domestic school formation of the adopted epoch. On the basis of review of normative documents leading tendencies and methodical Iuims of educational process and requirement to the teachers of drawing are traced.